(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
This article has the intention to implement a Balanced Scorecard (BSC) for a small company providing private security, nothing the contributions of this strategic management system as an auxiliary tool in the performance of the organization. Due to the existence of urgent application of performance measures no longer directed to the control, however focused on the strategic vision we chose a method that seeks to translate the strategic business vision. To achieve this goal, it adopted based on the strategic planning carried out in 2014/2015. In this sense, the methodological support to be the best direction to be followed by the company was given the administrative composition of strategic planning. It is noteworthy that some adjustments were necessary in the existing plan, to ensure greater truth of the reality of the company to start the Balanced Scorecard.